1961
DOI: 10.1038/icb.1961.10
|View full text |Cite
|
Sign up to set email alerts
|

ANALYSIS OF MAJOR HISTOCOMPATIBILITY FACTORS IN A STOCK OF CLOSELY INBRED WHITE LEGHORN FOWLS USING A GRAFT‐versus‐HOST REACTION ON THE CHORIOALLANTOIC MEMBRANE

Abstract: SUMMARY A study of two sublines of a closely inbred White Leghorn stock has been made using the number of foci produced after transfer of adult leucocytes to chorioallantoic membranes as an indication of the degree of genetic difference between donor and embryonic host. If minor degrees of reactivity are neglected for the time being, the results are explicable in terms of three alleles, A, B, C, at a single locus, and following clonal selection theories of immunity, on the assumption that each fowl carries leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1962
1962
1977
1977

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…Previous studies on the Simonsen phenomenon have shown conclusively that it fulfils all the criteria of a graft versus host reaction, namely, that the reaction is initiated by immunologieally competent donor cells (Szenberg and Warner, 1962) under the stimulation of a foreign host antigen (Burnet and Burnet, 1961), the reaction occurring in an immunologically incompetent host. Several other properties might be ascribed to graft versus host reactions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies on the Simonsen phenomenon have shown conclusively that it fulfils all the criteria of a graft versus host reaction, namely, that the reaction is initiated by immunologieally competent donor cells (Szenberg and Warner, 1962) under the stimulation of a foreign host antigen (Burnet and Burnet, 1961), the reaction occurring in an immunologically incompetent host. Several other properties might be ascribed to graft versus host reactions.…”
Section: Discussionmentioning
confidence: 99%
“…A point of interest that arises from this is the roughly twofold greater competence of the blood from another inbred line (designated by the genotype of CC, Burnet and Burnet, 1961), over AA blood when inoculated onto non-inbred membranes (Szenberg and Warner, 1962). This could possibly represent a similar situation to that described by Schierman and Nordskog (1963) in that with AA blood on non-inbred (AX) membranes, there is, on a selective approach, only one population of cells capable of reaction, whereas with the CC blood on (AX), provided the X is not the C genotype (which would be most unlikely as it would mean most outbred birds were AC), then two preadapted populations will be stimulated, thus giving twice the competence of AA donors on noninbred membranes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…
The formulation of natural selection theories of immunity (1-3) has stimulated intensive investigation of the cellular dynamics of antibody production in a number of laboratories (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Although determinations of the activity of isolated, single cells offer a direct approach (15-17), such analyses have thus far been limited to cells from secondarily stimulated animals.
…”
mentioning
confidence: 99%